Respostas

2013-12-10T11:31:57-02:00
Dividindo-se P(x) = 2x5 – x4 + x2 por (2x+3), encontramos como quociente e resto, respectivamente:
) Q(x) = 2x4 – 4x3 + 6x2 – 8x + 12 e R = -18
b) Q(x) = x4 – 2x3 + 3x2 – 4x + 6 e R = -9
c) Q(x) = 2x4 – 4x3 + 6x2 – 8x + 12 e R = -9
d) Q(x) = x4 – 2x3 + 3x2 – 4x + 6 e R = -18
e) Q(x) = x4 – 4x3 e R = 7

resposta
2x5 – x4 + x2                            |  2x+3
-2x5 - 3x4                            x4 – 2x3 + 3x2 – 4x + 6
/ -4x4 + x2
   4x4 + 6x3
 / 6x3 + x2
  -6x3 – 9x2 
  /  -8x2
  8x2 – 12x 
 /  -12x
     12x -18  
   /  -18
3 3 3